Cyclopamine–Paclitaxel‐Containing Nanoparticles: Internalization in Cells Detected by Confocal and Super‐Resolution Microscopy. Issue 9 (10th June 2015) - Fumagalli, Gaia; Mazza, Davide; Christodoulou, Michael S.; Damia, Giovanna; Ricci, Francesca; Perdicchia, Dario; Stella, Barbara; Dosio, Franco; Sotiropoulou, Panagiota A.; Passarella, Daniele
Abstract Cyclopamine‐ and paclitaxel‐containing hetero‐nanoparticles generated by self‐assembly show combined efficacy in the treatment of three different cancer cell lines. The use of ternary combination with the addition of a dye‐squalene conjugate secured the obtainment of fluorescent nanoparticles that permitted the observation of the cellular internalization by confocal microscopy and super‐resolution dSTORM (direct stochastic optical reconstruction microscopy).